Answer:
[tex] y= x^2 -6x +(\frac{6}{2})^2 +14 -(\frac{6}{2})^2[/tex]
And solving we have:
[tex] y= x^2 -6x +9 + 14 -9[/tex]
[tex] y= (x-3)^2 +5[/tex]
And we can write the expression like this:
[tex] y-5 = (x-3)^2[/tex]
The vertex for this case would be:
[tex] V= (3,5)[/tex]
And the minimum for the function would be 3 and there is no maximum value for the function
Step-by-step explanation:
For this case we have the following equation given:
[tex] y= x^2 -6x +14[/tex]
We can complete the square like this:
[tex] y= x^2 -6x +(\frac{6}{2})^2 +14 -(\frac{6}{2})^2[/tex]
And solving we have:
[tex] y= x^2 -6x +9 + 14 -9[/tex]
[tex] y= (x-3)^2 +5[/tex]
And we can write the expression like this:
[tex] y-5 = (x-3)^2[/tex]
The vertex for this case would be:
[tex] V= (3,5)[/tex]
And the minimum for the function would be 3 and there is no maximum value for the function